Character Education in Primary Schools and the New Implementation Education Method of Positive Behavioural Interventions and Supports (PBIS) in the Czech Republic - Michaela Pachelová (Theology and Philosophy of Education, 2023)
This article examines character education, which has been assessed as essential for the emotional and social development of children. Character education is included in the curriculum as early as preschool, and it should optimally continue in primary school. Furthermore, the importance of a correct choice of methods and guided reflections is also included. The article also discusses previous experiences with character education and the recommendations provided by the Czech School Inspectorate.